Efficacy and Safety of Innovative Experimental Chimeric Antigen Receptor (CAR) T-cells versus Axicabtagene ciloleucel (Yescarta) for the Treatment of Relapsed/Refractory Large B-Cell Lymphoma (LBCL): Matching Adjusted Indirect Comparisons (MAICs) and Systematic Review - Bayarmagnai Weinstein; Bogdan Muresan; Sara Solano; Antonio Vaz de Macedo; YoonJung Lee; Yu-Chen Su; Yeseul Ahn; Gabriela Henriquez; Christina Carmago; Gwang-Jin Kim; David O. Carpenter (University of Minnesota Libraries Publishing, 2021)
Despite favorable results of CAR T-cell therapy for relapsed/refractory large B-cell lymphoma (R/R LBCL), several challenges remain, including incomplete response, immune-mediated toxicity, and antigen-loss relapse. We delineated the relative clinical benefit of the novel approaches compared to the currently approved CAR T-cell therapies. In the absence of head-to-head comparisons and randomized controlled trials, we performed Matching Adjusted Indirect Comparisons to quantify the relative efficacy and safety of experimental CARs against Axicabtagene ciloleucel (Yescarta), the first FDA-approved CAR. A total of 182 R/R LBCL patients from 15 clinical trials with individual patient data (IPD) were pooled into eight populations by their CAR T-cell constructs and +/- ASCT status. The study endpoints were Progression-Free Survival (PFS), grade ≥ 3 cytokine release syndrome (CRS), and grade ≥ 3 neurotoxicity (NT). Tandem CD19.CD20.4-1BBζ CARs indicated favorable efﬁcacy and safety, whereas the co-infusion of CD19 & CD20 with 4-1BBζ showed no clinical benefit compared to Yescarta. Third generation CD19. CD28. 4-1BBζ, and sequential administration of autologous stem cell transplantation (ASCT) and CD19. CARs presented statistically insignificant yet improved PFS and safety except for ASCT combined intervention which had suggestively higher NT risk than Yescarta. CARs with modified co-stimulatory domains to reduce toxicity (Hu19. CD8.28Zζ and CD19. BBz.86ζ) presented remarkable safety with no severe adverse events; however, both presented worse PFS than Yescarta. Third-generation CARs demonstrated statistically significantly lower NT than Yescarta. CD20. 4-1BBζ data suggested targeting CD20 antigen alone lacks clinical or safety benefit compared to Yescarta. Further comparisons with other FDA-approved CARs are needed.